Comparison of larval eating capacity of two indigenous larvivorous fishes in malaria vector control in laboratory conditions in Dogbo district in south-western Benin, West Africa - Agblonon, Thierry Matinkpon; Aïzoun, Nazaire; CHOUGOUROU, CHÈPO DANIEL (My University, 2022)
Because of problems with insecticide resistance, alternative malaria control methods were necessary. These methods include the use of biological control agents, such as larvivorous fish. This study aimed to compare the larval eating capacity of two indigenous larvivorous fishes in malaria vector control in laboratory conditions in Dogbo district in south-western Benin. Larvae of Anopheles gambiae sensu lato mosquitoes were collected from breeding sites using the dipping method in July 2020 during the rainy season in Dogbo district. Alive Clarias gariepinus and Orechromis niloticus fishes were bought immediately once catched by fishers of Ganvié location in So-Ava district and carried by car from Ganvié location to the Laboratory. Laboratory evaluation for larvivorous efficacy was conducted. The results obtained in the current study showed that the larval eating capacity of Clarias gariepinus fish when this fish was fed was higher than that of Orechromis niloticus indigenous larvivorous fish in the laboratory conditions. Similar results were obtained when these different fishes were unfed. In a context of environmental crisis and global changes, environmentally friendly methods should be encouraged. The use of indigenous larvivorous fishes as predators to control malaria mosquitoes is obviously insufficient in the current study.
Keywords: Clarias gariepinus; Orechromis niloticus; larvae of Anopheles gambiae s.l; Malaria vectors; Benin